Monitoring COVID-19 Impacts on Households in Ethiopia, Report No. 5 : Gendered Impacts of the COVID-19 Pandemic in Ethiopia - Results from a High-Frequency Phone Survey of Households - Ebrahim, Menaal (World Bank, Washington, DC, 2020)
The analysis is based on a sample of 3,058 households in both urban and rural areas in all regions of Ethiopia. The 15-minute interview covers a diverse set of topics such as access to basic services, child educational activities during school closures, employment dynamics, household income and livelihood, income loss and coping strategies, food security and assistance received. In this brief, we focus on topics where gendered differences were striking.